1996
DOI: 10.1002/hlca.19960790718
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Diselenides from Benzylamines: Catalysts in the Diethylzinc Addition to Aldehydes

Abstract: A series of new chiral diselenides with a N-atom in the side chain was prepared by a short synthetic sequence (Scheme 1). Only 1 mol-% of these diselenides catalyzed very effectively the diethylzinc addition to various aromatic and a$-unsaturated aldehydes yielding the secondary alcohols in up to 98 % ee (Scheme 2 and Tables 1 and 2). An asymmetric amplification was observed with these catalysts. Detailed NMR studies were performed to characterize the catalytically active species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 28 publications
0
31
0
1
Order By: Relevance
“…Wirth and co-workers have shown that diselenide 28 with a monomethylated amino moiety can be synthesized through the ortho-lithiation route by using tBuLi as the lithiating agent. [14] Singh and co-workers reported the synthesis of diselenide 29 by reduction of the corresponding azomethine diselenide, which was prepared from bis(o-formylphenyl)diselenide. [15] It is known that the reactions of 2-(chloroseleno)benzoyl chloride (30) with various amines produce ebselen analogues in good yield, [6b] and this methodology can be used to synthesize diselenides having sec-amido moieties.…”
Section: Resultsmentioning
confidence: 99%
“…Wirth and co-workers have shown that diselenide 28 with a monomethylated amino moiety can be synthesized through the ortho-lithiation route by using tBuLi as the lithiating agent. [14] Singh and co-workers reported the synthesis of diselenide 29 by reduction of the corresponding azomethine diselenide, which was prepared from bis(o-formylphenyl)diselenide. [15] It is known that the reactions of 2-(chloroseleno)benzoyl chloride (30) with various amines produce ebselen analogues in good yield, [6b] and this methodology can be used to synthesize diselenides having sec-amido moieties.…”
Section: Resultsmentioning
confidence: 99%
“…A positive nonlinear relationship (asymmetric amplification) between the optical purities of the catalyst and the product was observed. [70] Other selenium-containing catalysts such as 76 (Fc* ferrocenyl moiety 62 b) leading to enantioselectivities up to 94 % in the products 74 have been investigated as well in this addition reaction. [71] Palladium-catalyzed allylic substitutions can be performed with catalysts containing a selenium atom, but the selectivites obtained are lower than with the chiral phosphorus-containing ligands usually employed in these reactions.…”
Section: Catalytic Reactionsmentioning
confidence: 99%
“…1,75,76 To elucidate the mechanistic aspects, we assumed that the disulfide linkage is cleaved by nucleophilic attack of diethylzinc, resulting in the thiolate 5 and the thioether 6 (Scheme 2), according to the results reported by Kellogg 35 and Wirth. 30 Aiming to identify the catalytically active species, we prepared the compound 6 via 2a ring-opening reaction by attack of EtSSEt/NaBH 4 77 as shown in Scheme 3. We believe that the active catalyst of the reaction is the species 5, since in an additional experiment, the thioether 6 did not catalyze the alkylation reaction of benzaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28][29][30][31][32] Sulfur containing ligands 33 like b-amino thiols and b-amino disulfides derivatives from ephedrine, [34][35][36] norephedrine, [37][38][39] (S)-proline, [40][41][42] (S)-phenylglycine, 43 (S)-valine, 44,45 (R)-cysteine, 5,46-50 (R)-cystine, 51 and others [52][53][54][55][56][57][58] have gained more and more interest as catalysts in this stereoselective reaction. In a similar way, chiral amino diselenides have been efficiently used as catalysts for this addition, [28][29][30][31][32] but due to the most difficult accessibility of these compounds, only a few number of reports can be found in literature.…”
Section: Introductionmentioning
confidence: 99%